A Weighted Cluster Head Selection Algorithm for Energy Efficient Wireless Sensor Networks. (6th May 2022) - Ali, Syed Asif; Sarfraz, Mubashar; Ghauri, Sajjad A.; Mahmood, Asad; Basir, Shahid; Kebedew, Teweldebrhan Mezgebo; Alam, Sheraz
Abstract : The wireless sensor network's (WSNs) lifetime is mainly dependent on the RE of the sensor nodes (SeN). In recent years, energy minimization in a WSN has been a prominent research topic, and numerous solutions have been proposed. This research focuses on the energy minimization of the SeNs where firstly, K-medoid clustering algorithm is applied to create clusters. Second, a weighted cluster head selection technique is used to choose a cluster head (CH) by integrating three independent weights associated with an SeN: energy, distance from the centroid, and distance from the sink node (SN). According to the energy level and distance from the SN and cluster's centre, each node is assigned a constant weight. The simulation results are compared to existing methodologies, and the results show that the suggested network's lifetime enhances.